Text and Image Watermarking Using Random Significant Bit - Pahadiya, Y; Khatri, R (International Journal of Computer Sciences and Engineering, 2025)
Security of Multimedia is very challenging task in today because data move over Internet. Anyone can easily hack or misuse the data specially images. So hide data such as text document, images, and audio, video in to digital images. In this paper, we proposed random significant bit (RSB) method for text or image watermarking. Random significant bit method and least significant method implemented using java. Compare random significant bit method and Least Significant method on the basis of time. Found that random significant bit method take less time compare to Least Significant method.